Intracerebral Hemorrhage Therapeutics Concepts and Customs (Springer International Publishing, 2018)
This book provides a framework for goal-targeted management of the adult patient with spontaneous non-traumatic intracerebral hemorrhage (ICH). Topics addressed in a comprehensive yet practical manner in the book include pre-hospital/emergency department care, early inpatient work-up, antithrombotic- and thrombolytic-related strokes, optimal blood pressure management, avoidance of medical complications, surgical interventions, outcome prognostication, recurrence prevention, rehabilitation/recovery, special situations, systems of care, and the design of clinical trials for patients with ICH. Procedures, processes, and helpful decision-making algorithms are presented with the aid of complementary illustrations that facilitate understanding of practical aspects and enable the reader to promptly retrieve relevant information. In addition, the most current evidence-based therapies for routine management of ICH patients and a glimpse of promising future treatment strategies are reviewed. Timely and consolidated, clinicians will find this to be an indispensable resource to navigating the ever-increasing pace of discovery that is transforming what we know about ICH and its treatment. .